CYBERCRIMES COMMITTED THROUGH PHISHING AND RANSOMWARE ATTACKS IN UZBEKISTAN: ANALYSIS AND PROTECTIVE MEASURES - Qobilov Shokir Anvarovich (Scholar Express Journals, 2025)
In recent years, due to the rapid development of information technologies and artificial intelligence, cybercrime has taken on new forms and content. In particular, cyberattacks carried out using artificial intelligence - phishing, ransomware, deepfake, botnets and automated attacks - pose a serious threat to the security of society and individuals. This article provides a detailed analysis of the state of modern cybercrimes in Uzbekistan, their mechanisms of implementation, the level of distribution, consequences, and measures that are being used and should be taken against them. In particular, cybercrimes such as illegal seizure of personal data, hacking of financial accounts, false information sent via e-mail (phishing), and software encryption and ransom demands (ransomware) are comprehensively analyzed. The article presents international experiences, legal mechanisms, technical and preventive approaches to ensuring cybersecurity. At the same time, the need to increase the culture of information security and raise the digital awareness of the population and organizations is emphasized. This study includes scientific and practical proposals and recommendations aimed at strengthening the fight against cybercrime and improving the state security system in Uzbekistan.
Keywords: Cybercrime; information security; artificial intelligence